2019
DOI: 10.1155/2019/6026719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulforaphane on Bladder Compliance in a Rat Model of Partial Bladder Outlet Obstruction

Abstract: Aims. To investigate the effect of Nrf2 activator sulforaphane (SFN) on bladder compliance and the underlying mechanisms in a rat model of partial bladder outlet obstruction (BOO). Methods. Male 8-week-old Sprague-Dawley rats were divided into three groups. BOO rats were given daily 0.5 mg/kg sulforaphane (BOO+SFN) or vehicle (BOO) intraperitoneally for 4 weeks, while sham-operated rats were treated with vehicle (Sham). Bladder compliance, histological alteration, and collagen deposition were evaluated. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Many studies have indicated that ECM deposition increases after pBOO, leading to decreased bladder compliance. 22 Moreover, in an investigation of the impact of Thbs1 on the ECM, normal human urinary epithelial cells were stimulated with TGF-β1 to establish an in vitro fibrosis model. 23 In this study, we found that Fn and MMPs were highly expressed in SV-HUC-1 cells induced by TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that ECM deposition increases after pBOO, leading to decreased bladder compliance. 22 Moreover, in an investigation of the impact of Thbs1 on the ECM, normal human urinary epithelial cells were stimulated with TGF-β1 to establish an in vitro fibrosis model. 23 In this study, we found that Fn and MMPs were highly expressed in SV-HUC-1 cells induced by TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Functional enrichment analysis in the present study revealed that extracellular matrix-related functions were also significantly activated. Collagen I and III are the main factors of bladder compliance ( 45 ). Once collagen is heavily deposited in the bladder wall, elastin becomes relatively reduced, leading to thicker bladder walls, decreased smooth muscle function, reduced bladder compliance and even bladder fibrosis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Frontiers in Pharmacology frontiersin.org they found that SFN could alleviate pBOO-induced bladder injury by activating the Nrf2-ARE pathway, increasing the activity of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and catalase (CAT) to reduce oxidative stress, and lowering the B cell lymphoma 2 associated X protein (Bax)/B cell lymphoma 2 (bcl-2) ratio to inhibit apoptosis (Liu et al, 2016). In Liu et al's subsequent in vivo study (Liu et al, 2019), through treating BOO rat models with 0.5 mg/kg/day of SFN, they found that bladder compliance in BOO rats was significantly reduced. Further research found that SFN improved bladder compliance by upregulating matrix metalloproteinases-1 (MMP-1) and downregulating tissue inhibitors of metalloproteinases-1 (TIMP-1) expression.…”
Section: Sulforaphane and Bladder Outlet Obstruction: Bladder Protectionmentioning
confidence: 99%